224k views
15 votes
X + 6 = −x − 6
(so i can ask)kjhgfdccfghjk

User Domenica
by
5.3k points

1 Answer

2 votes

Answer:

x = -6

Explanation:

Equations

Solve the equation:

x + 6 = -x - 6

We must find the value of x that makes the identity above true.

Let's join all the variables on the left side and the numbers on the right side.

Adding x:

x + 6 + x = -x - 6 + x

The variables cancel out on the right side:

2x + 6 = -6

Subtracting 6:

2x + 6 - 6 = -6 -6

The 6 and -6 are canceled out:

2x = -12

Dividing by 2:

x = -12/2

x = -6

User TheGuyWithTheFace
by
5.2k points